PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, LEVERAGE DAN NILAI PERUSAHAAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Purba, Rolita Christina (JURNAL GLOBAL MANAJEMEN; Vol 9 No 1 (2020): JUNI, 2020)
This study aims at determining the effect of corporate governance, profitability, leverage and corporate value on tax avoidance in companies listed on the Indonesia Stock Exchange for 2017 - 2019. Applying tax regulation correctly and appropriately is an efficient business in achieving profit. There are two tax managements, namely tax avoidance and tax evasion. In this study, researchers examined the tax avoidance section. This research was conducted on chemical sub-sector manufacturing companies listed on the Stock Exchange period 2017 - 2019. The population in this study is all chemical sub-sector companies listed on the Stock Exchange as many as 26 companies. The sampling technique in this study uses a census, where all populations are sampled. The testing method in this study uses the classic assumption test and linear regression. The results of this study indicate that profitability and leverage have a significant relationship to tax avoidance, while corporate governance and corporate value do not have a significant relationship to tax avoidance on companies listed on the Indonesia Stock Exchange.